Ethnic/Diasporic/Transnational: The Rise and Fall of ImaginAsian TV. (March 2018) - Han, Benjamin
This article examines the rise and fall of ImaginAsian TV to illustrate the travails of imagining a broadcast community of Asian Americans and the potential effect this has on the politics of representation. Drawing on institutional politics, media history, and oral interviews, the article analyzes the problematic conceptualization of a homogeneous Asian American audience, and further explicates how the usage of the English language in ImaginAsian's programming strategy, despite its syndicated programs in different Asian languages, could not accommodate the disparate but interconnected cultural logics of transnationalism, race and ethnicity, and diaspora which structure Asian and Asian American identities.